OP0192 Adding ultrasound to the treat-to-target strategy shows no benefit in achievement of remission: results from the biodam cohort. (15th June 2017) - Sepriano, A; Ramiro, S; Landewé, R; Heijde, D van der; Ohrndorf, S; FitzGerald, O; Backhaus, M; Larché, M; Homik, J; Saraux, A; Hammer, H; Terslev, L; et al.
Abstract : Background: While, a Treat-to-Target strategy (T2T), treating patients with rheumatoid arthritis (RA) towards a certain target (eg. clinical remission; T2T-REM), is highly recommended, several patients in clinical remission often have residual synovitis on ultrasound-imaging (US). This may result in silent radiographic progression and clinical flare. It is arguable whether targeting US-synovitis may result in "deeper" remission in clinical practice. Objectives: To assess whether using US in a T2T strategy leads to more patients meeting clinical remission than using only clinical information. Methods: Patients with RA who started or changed csDMARD and/or anti-TNF treatment followed in centers with expertise in US and participating in BIODAM (2-year multicenter prospective observational cohort) were included. Clinical and US data [by the US7-score that includes 7 joints of the clinically dominant hand and foot for synovitis and tenosynovitis on gray-scale US (GSUS) and power-doppler US (PDUS) and erosions on GSUS] were collected every 3 months. Per visit was decided whether the patient was treated according to the clinical definition of T2T with remission as benchmark (T2T-CLIN-REM). Though not mandatory, US-data could also be used for this purpose. T2T-CLIN-REM was considered correctly applied if: either i) a patient already had a disease activity score below the remission target (i.e. ACR/EULAR boolean remission) or ii) if not, treatment was intensified. A T2T strategy taking also US data into account (T2T-CLIN-US-REM) was considered correctly applied if: either i) both clinical and US remission (all joints included in the US7-score with GSUS synovitis <2 and PDUS synovitis=0) were present; or ii) if not, the treatment was intensified. The main outcome was ACR/EULAR boolean remission. The effect of adding US to T2T (T2T-CLIN-US-REM) on clinical remission 3 months later compared to a clinical remission benchmark only (T2T-CLIN-REM) was analyzed using generalized estimating equations with auto-regression. Results: In total 963 visits of 130 patients were included. T2T-CLIN-US-REM was correctly followed in 33% of the visits, T2T-CLIN-REM in 14%, and any of these in 52%. Remission according to the ACR/EULAR-boolean definition was achieved in 19.6% of the visits. Compared to the conventional T2T-CLIN-REM strategy, using a combined clinical and US benchmark for T2T led to a lower – instead of higher - likelihood of ACR/EULAR-boolean remission 3 months later [OR (95% CI): 0.39 (0.24; 0.63] (table). Conclusions: Our results, from a non-randomized study, did not suggest an advantage of using US of 7 joints in addition to clinical examination as a T2T benchmark as compared to clinical examination alone in getting RA patients into clinical remission. Disclosure of Interest: None declared